(3GdQSGdI GdeLOhdI aj GdGSJKfGAGJ GdeSdSdIs - (3SQGL GdOjfs ((3YHOGdcQje Hf eMeO s)
(3ChdgG (B:s
(3CeG HYO, abO habfj MSf GdGJaGb aj HYV eLGdS HCPQHjLGf hYQGbg deMGhQI aFI MfcJge GdYdhe GdMbjbjI s
(3BNQgG (B:s
(3ade jLJeYG HMSH GbJVGA hGMO, MJi jchf eMPhQkG hgh BNQ eG LGA Hg Pgfj hSeM Hg NGWQj hCQLh Cf jchf UhGHkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfj hGdCNjQs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B144 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs